Mewujudkan Karakter Peserta Didik Melalui Model Talking Stick - Salayan, Madyunus; Sari, Dwi Novita; Yunanda, Erni; Fauzi, Ahmad (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2023)
Elementary School is one of the levels of Education that has an important task in shaping the character of students. We see that the current generation looks very lacking in character. This phenomenon gives encouragement to the government to change the purpose of the education curriculum towards the formation of student character. The purpose of PKM is to find the values needed by teachers for the formation of students' character by using the talking stick model. The talking stick model is a learning model that gives students the freedom to be able to act freely as far as possible without coercion so that they can develop confidence. This model is expected to shape the character of students. The method of this activity is a lecture and question and answer about the socialized stick takling model. Socialization of models that can be used as one of the alternatives in learning in order to shape the characteristics of students. Counseling on the socialization of the talking stick model was carried out at SDN 101808 Candirejo Village, Biru-Biru District, Deli Serdang Regency. This counseling activity is expected to shape the characteristics of students since gaining knowledge at school. The results of this counseling are expected so that teachers can shape the character of students to be better by using the talking stick model.